Database search of spontaneous reports and pharmacological investigations on the sulfonylureas and glinides-induced atrophy in skeletal muscle - Mele, Antonietta (Blackwell Publishing Ltd, 2014)
The ATP-sensitive K(+) (KATP) channel is an emerging pathway in the skeletal muscle atrophy which is a comorbidity condition in diabetes. The “in vitro” effects of the sulfonylureas and glinides were evaluated on the protein content/muscle weight, fibers viability, mitochondrial succinic dehydrogenases (SDH) activity, and channel currents in oxidative soleus (SOL), glycolitic/oxidative flexor digitorum brevis (FDB), and glycolitic extensor digitorum longus (EDL) muscle fibers of mice using biochemical and cell-counting Kit-8 assay, image analysis, and patch-clamp techniques. The sulfonylureas were: tolbutamide, glibenclamide, and glimepiride; the glinides were: repaglinide and nateglinide. Food and Drug Administration-Adverse Effects Reporting System (FDA-AERS) database searching of atrophy-related signals associated with the use of these drugs in humans has been performed. The drugs after 24 h of incubation time reduced the protein content/muscle weight and fibers viability more effectively in FDB and SOL than in the EDL. The order of efficacy of the drugs in reducing the protein content in FDB was: repaglinide (EC50 = 5.21 × 10(−6)) ≥ glibenclamide(EC50 = 8.84 × 10(−6)) > glimepiride(EC50 = 2.93 × 10(−5)) > tolbutamide(EC50 = 1.07 × 10(−4)) > nateglinide(EC50 = 1.61 × 10(−4)) and it was: repaglinide(7.15 × 10(−5)) ≥ glibenclamide(EC50 = 9.10 × 10(−5)) > nateglinide(EC50 = 1.80 × 10(−4)) ≥ tolbutamide(EC50 = 2.19 × 10(−4)) > glimepiride(EC50=–) in SOL. The drug-induced atrophy can be explained by the KATP channel block and by the enhancement of the mitochondrial SDH activity. In an 8-month period, muscle atrophy was found in 0.27% of the glibenclamide reports in humans and in 0.022% of the other not sulfonylureas and glinides drugs. No reports of atrophy were found for the other sulfonylureas and glinides in the FDA-AERS. Glibenclamide induces atrophy in animal experiments and in human patients. Glimepiride shows less potential for inducing atrophy.